False Propaganda as a Tool for Toppling Political Regimes: A Study in Light of Public International Law - Adnan Adadi, Assist. Lect. Huda (Basra studies journal, 2026)
False propaganda is one of the most dangerous tools used in psychological and media warfare to weaken or overthrow political regimes. It aims to shape and manipulate public opinion by disseminating misleading, exaggerated, or distorted information. Although political propaganda has existed since the earliest human conflicts, technological and digital advancements have extended its impact beyond the traditional boundaries of states. This study analyzes the concept and dimensions of false propaganda, highlighting its role in undermining the legitimacy of political regimes. It further examines the legality of such practices under public international law, with particular emphasis on principles related to non-intervention in domestic affairs, the prohibition of war propaganda, and the protection of international peace and security. Furthermore, the study offers a critical legal assessment of the challenges arising from the use of propaganda in international relations.